Influence of crop rotation on rice yield and environmental protection - Ilieva, Verica; Andov, Dobre; Andreevska, Danica; Zaševa, Tanja (Macedonian Journal of Ecology and Environment, 2007)
The yield of paddy, the dressing percentage of white rice and the total yield of white rice were investigated in monoculture of growing rice and crop rotation. Experiments were carried out at two locations: Bosevica (Institute of Agriculture-Skopje, Rice Department-Kocani) and Laka (Agro-iskra, Kocani and Moteks-Zrnovci) during 2002, 2003 and 2004 The results show that the rice can tolerate the monoculture but when it’s grown in crop rotation and lower agrotechnic it gives better results which has special significance from the aspect if healthy food production and protection of the environment.